2021
DOI: 10.3390/jfmk6040084
|View full text |Cite
|
Sign up to set email alerts
|

Protections in the Recreational Practice of Ski and Snowboard—An Age and Gender Discussion? A Case Study in Spain

Abstract: The objective of this research was to evaluate the protections taken by ski and snowboard recreational athletes of the winter stations Sierra Nevada and Alto Campoo (Spain), regarding gender, age, and practiced sport. A total of 520 users participated, Sierra Nevada (n = 306 (58.8%)); Alto Campoo (n = 214 (42.2%)), 257 of them were men (49.4%) and 263 (50.6%) were women, from 6 to 64 years old, classified by 4 stages of development (Childhood (n = 106 (20.4%)); Teenagers (n = 110 (21.2%)); Youth (n = 101 (19.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…However, more than 25% of skiers and snowboarders do not use it [ 15 ]. Likewise, a recent study conducted by Mecías-Calvo and colleagues [ 16 ] showed similar data (23.5%). Nevertheless, this study showed that the use of this protection was age and gender-dependent.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, more than 25% of skiers and snowboarders do not use it [ 15 ]. Likewise, a recent study conducted by Mecías-Calvo and colleagues [ 16 ] showed similar data (23.5%). Nevertheless, this study showed that the use of this protection was age and gender-dependent.…”
Section: Introductionsupporting
confidence: 75%
“…Nevertheless, this study showed that the use of this protection was age and gender-dependent. That is, children and teenagers used more protective equipment than older ones, and women were more prone to use protections than men [ 16 ].…”
Section: Introductionmentioning
confidence: 99%